Change in left atrial function predicts incident atrial fibrillation: the Multi-Ethnic Study of Atherosclerosis. (29th July 2019) - Lim, Daniel J; Ambale-Ventakesh, Bharath; Ostovaneh, Mohammad R; Zghaib, Tarek; Ashikaga, Hiroshi; Wu, Colin; Watson, Karol E; Hughes, Timothy; Shea, Steven; Heckbert, Susan R; Bluemke, David A; Post, Wendy S; et al.
Abstract: Aims: Longitudinal change in left atrial (LA) structure and function could be helpful in predicting risk for incident atrial fibrillation (AF). We used cardiac magnetic resonance (CMR) imaging to explore the relationship between change in LA structure and function and incident AF in a multi-ethnic population free of clinical cardiovascular disease at baseline. Methods and results: In the Multi-Ethnic Study of Atherosclerosis (MESA), 2338 participants, free at baseline of clinically recognized AF and cardiovascular disease, had LA volume and function assessed with CMR imaging, at baseline (2000–02), and at Exam 4 (2005–07) or 5 (2010–12). Free of AF, 124 participants developed AF over 3.8 ± 0.9 years (2015) following the second imaging. In adjusted Cox regression models, an average annualized change in all LA parameters were significantly associated with an increased risk of AF. An annual decrease of 1-SD unit in total LA emptying fractions (LAEF) was most strongly associated with risk of AF after adjusting for clinical risk factors for AF, baseline LA parameters, and left ventricular mass-to-volume ratio (hazard ratio per SD = 1.91, 95% confidence interval = 1.53–2.38, P  < 0.001). The addition of change in total LAEF to an AF risk score improved model discrimination and reclassification (net reclassification improvement = 0.107, P  = 0.017; integrative discrimination index = 0.049, P  < 0.001). Conclusion: In this multi-ethnic study population free of clinical cardiovascular disease at baseline, a greater increase in LA volumes and decrease in LA function were associated with incident AF. The addition of change in total LAEF to risk prediction models for AF improved model discrimination and reclassification of AF risk.